2008
DOI: 10.1017/s0265021508004870
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous extracorporeal lung assist as integral part of a multimodal treatment concept

Abstract: A multimodal treatment concept with arteriovenous extracorporeal lung assist as its central part provides reversal of hypercapnia and stabilization of oxygenation. In an attempt to maximize lung protection and potentially reduce ventilator-induced lung injury, a further VT reduction below 4 mL kg(-1) predicted body weight combined with a high mean airway pressure and continuous axial rotation is safely possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Two studies reported VFDs [18,27]. The primary outcome measure in the Xtravent study was VFDs to 28 and 60 days [19].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies reported VFDs [18,27]. The primary outcome measure in the Xtravent study was VFDs to 28 and 60 days [19].…”
Section: Reviewmentioning
confidence: 99%
“…Five studies (two RCTs and three retrospective studies) reported ICU length of stay [18,19,26,27,29]. Neither RCT demonstrated a significant reduction in ICU length of stay.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…An increased ventilation rate may allow only to compensate in part for the decrease in tidal ventilation resulting in hypercapnic acidosis [4], [7], [9]. There is some evidence from cell culture and animal studies including our own studies using this surfactant depletion model (unpublished data), that hypercapnic acidosis itself induced by administration of carbon dioxide to the inspired air (so called therapeutic hypercapnia) protects the lung [14][16] and increases oxygen delivery to the tissues [17].…”
Section: Introductionmentioning
confidence: 95%